Factors affecting sustainability of municipal solid waste composting projects in Sri Lanka - Sinnathamby, V.; Paul, Johannes G.; Dasanayaka, S.W.S.B.; Gunawardena, S. H. P.; Fernando, Sudarshana (2016)
During the past decades, many composting projects have been implemented with the assistance from various donor agencies to address the municipal solid waste (MSW) problem in developing countries, especially in urban areas. However, very few of these projects are sustainable and many were reported as failures, some even closed down and most ofexisting operations rely on heavy subsidies from the Government, foreign funding sources and Local Authorities (LAs). To enhance solid waste management (SWM) an initiative called "Pilisaru" project started in 2008 lead by the Central Environmental Authority (CEA) to develop the infrastructures of LAs for a better S WM system mainly focllsing on composting as an efficient low cost option for treatment of the organic waste fraction. However, the initial assessment of this initiative encountered many issues. Therefore, this study was proposed to identifY main lactors that affect the sustainability of municipal compost plants. The methods used to obtain data for this research comprise, sample survey that involved five selected compost plants operating under LAs in Sri Lanka; a specific lield survey that observed waste segregation activities: and a cl ients perception survey conducted in a super market in Colombo that aimed to assess customers perspective 011 buying and use ofcompost based I"bod products. To supplement the findings ofthese investigations, a complementary literature revie\\ and selected expert interviews were carried out with representative stakeholders. The research findings indicate that most of LAs do not have the needed expertise to design, implement and manage an integrated S WM system that allows efticient operation of compost plants according to recognized standards. Furthermore, it appears that 1110st ofthe compost plants do not manage it full-cost recovery of their O&M cost with the main issues that users are not charged for the provided waste management services and .produced compost can not be marketed successfully, Besides, from the perspective of sustainable operation, need and provision offuture investment is unclear, especially for replacement to maintain an effective operation level. To overcome the emerging weaknesses of the Pilisaru project, it is recommended to provide a continuous capacity building programme for the LAs and involved stakeholders, supported by public awareness programs, especially lor enhanced waste segregation, marketing promotion for compost products as well as technical and financial assistance for relevant stakeholders that need support to perform their tasks in the SW value chain. Furthermore, it is envisioned to revisit the provided SWM policies and to add regulations that built on insights from best SWM practices in Sri Lanka but also from applicable international experiences from other developing countries. This should also include the production of quality compost that meets the fertilizer demands from an agriculture perspective. Lastly, the enhancement of waste segregation practices and involvement of the private sector should be addressed in order to strengthen operations and business performance through enhanced public participation and Private-Public-Partnerships (PPP).